Determinants of Effective Tax Rates in Indonesia’s Energy Sector - Andika, Andika; Yantiana, Nella; Espa, Vitriyan; Kurniawan, Rudy; Rusmita, Sari; Ardimansyah, Ardimansyah (SENTRI: Jurnal Riset Ilmiah, 2025)
Taxes serve as a fundamental source of state revenue, contributing to economic growth and enhancing societal well-being. However, the challenges of increasing tax revenue have become increasingly complex, especially in the energy sector, which significantly contributes to the national budget. This study examines how capital intensity, firm size, and Return on Assets (ROA) affect the Effective Tax Rate (ETR). This study examines firms listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023, collecting data through purposive sampling. The data analysis employs multiple regression methods using panel data. The results indicate that capital intensity has a negative impact on ETR, firm size does not contribute significantly, and ROA also negatively affects ETR. These findings imply that the government can formulate strategies to address tax evasion in the energy sector, thereby optimizing tax revenue for the state